KULTURMØDER TIL FORHANDLING: Betydningen af ‘kultur’ i praktiksamtaler med voksne med dansk som andetsprog - Tranekjær, Louise (Tidsskriftet Antropologi, 2007)
The article demonstrates how the combination of discursive psychology and conversation analysis enables an examination of culture as a product of discursive processes which are influenced and permeated by a broader social, discursive and cultural context. In this way an understanding is presented of cultural encounters as something which is not only determined by the background of the participants but is a product of interaction and the resources used in the negotiation of meaning and identity. The article is based on research of internship interviews, that is, interactions between Danish employers and adult second language speakers seeking an internship placement. Through examples from these interviews, it is argued that culture can be analyzed by combining a micro-perspective on the negotiation and organization of meaning in interaction with a macro-perspective on interactions as a manifestation of a broader social, discursive and cultural practice and organization.